Teologi Kemakmuran dan Problematika Hermeneutik Alkitabiah - Haryanto, Luciana; Suharso, Suharso (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This article aims to critically evaluate prosperity theology by highlighting the underlying biblical hermeneutical problems, especially in the use of key verses such as John 10:10 and Philippians 4:19. This study uses a qualitative approach with a library research method, through theological, historical, and hermeneutical analysis of relevant academic literature and theological sources. The results of the study show that prosperity theology contains serious weaknesses in its eisegetical and reductive interpretation of the Bible, thereby obscuring the meaning of the Gospel, which centres on the cross, suffering, and discipleship. Interpretations that are detached from the historical and linguistic context of the biblical text not only give rise to a materialistic understanding of blessings, but also have an impact on the crisis of spirituality, pastoral violence, and the weakening of church community solidarity. This article asserts that the problem of prosperity theology is not limited to doctrinal aspects, but reflects a hermeneutical and spiritual crisis in the contemporary church.